Sustainability of rice supply chain for Thai farmers - Sarajit, Chitralada (2016)
World rice consumption increases every year due to world population growth. This challenges rice producing countries to improve productivity. Moreover, high quality of rice with high nutrients and safety for farmers and consumers are considered in market trend. While recently, various factors more influence the volume of rice production such as climate change, diseases, insects, pollution in soil and water. This includes the increasing of inputs price, rice price volatility, the stability of the government and the lack of farming labours. Although, Thailand as a leader of rice exporter country, farmers are also facing difficulties of such factors. Therefore, the concept of sustainability is taken into consideration to improve rice supply chain, particularly rice production to help Thai farmers have ability to deal with any situations. The study aims to recommend sustainability of rice supply chain model and rice production practices in Thailand by information of other leaders of producing countries has been conducted and analysed. It includes opinions and recommendations from farmers’ leaders and rice specialists which they are useful to adapt the rice supply chain and rice production being practical. The new rice supply chain has no middleman between farmers and rice processors to decrease logistics cost and increase purchasing price for farmers more or less. Furthermore, farmers are highly recommended to join in either cooperatives group to have more power or contract farming to assure income. At the same time, farmers implement sustainable farming practices by government and relevant firms contribute with all their ability. Moreover, sustainability of rice supply chain will not achieve if there is no collaboration and information sharing.